CRISPR/Cas Systems‐Inspired Nano/Biosensors for Detecting Infectious Viruses and Pathogenic Bacteria. Issue 10 (16th September 2022) - Zhang, Xianlong; Shi, Yiheng; Chen, Guang; Wu, Di; Wu, Yongning; Li, Guoliang
Abstract: Infectious pathogens cause severe human illnesses and great deaths per year worldwide. Rapid, sensitive, and accurate detection of pathogens is of great importance for preventing infectious diseases caused by pathogens and optimizing medical healthcare systems. Inspired by a microbial defense system (i.e., CRISPR/ CRISPR‐associated proteins (Cas) system, an adaptive immune system for protecting microorganisms from being attacked by invading species), a great many new biosensors have been successfully developed and widely applied in the detection of infectious viruses and pathogenic bacteria. Moreover, advanced nanotechnologies have also been integrated into these biosensors to improve their detection stability, sensitivity, and accuracy. In this review, the recent advance in CRISPR/Cas systems‐based nano/biosensors and their applications in the detection of infectious viruses and pathogenic bacteria are comprehensively reviewed. First of all, the categories and working principles of CRISPR/Cas systems for establishing the nano/biosensors are simply introduced. Then, the design and construction of CRISPR/Cas systems‐based nano/biosensors are comprehensively discussed. In the end, attentions are focused on the applications of CRISPR/Cas systems‐based nano/biosensors in the detection of infectious viruses and pathogenic bacteria. Impressively, the remaining opportunities and challenges for the further design and development of CRISPR/Cas system‐based nano/biosensors and their promising applications are proposed. Abstract : The latest research advances in the design and construction of CRISPR/ CRISPR‐associated protein systems‐inspired nano/biosensors and their applications in the detection of infectious viruses and pathogenic bacteria are comprehensively summarized. Impressively, the most important challenges and opportunities remaining in this exciting area of research are proposed.